Bioactive compounds from selected medicinal plants used in antidiabetic treatment - Mngeni, Nasipi Zamanala (Cape Peninsula University of Technology, 2017)
The continued use and popularity of plant-based traditional medicine demands scientific validation of the therapeutic potential of the medicinal plants used in disease management and treatment. These medicinal plants are to be evaluated for phytochemical constituents and pharmacologically screened for their bioactivity and include the isolation and identification of their bioactive compounds. The diabetes tea and its eight individual plants constituents were collected from Sing Fefur Herbs in McGregor, Western Cape. The plant material was ground to a fine powder form using a milling machine. The powdered plant material was sequentially extracted with hexane, 1:1 DCM, DCM:MeOH, MeOH and water. The antioxidant activity of the tea and its plants was evaluated with comparison to the antioxidant activity of brewed rooibos tea in literature. The concentration of antioxidants in the plants and the tea were found to be significantly high. The ORAC assay results of the water extracts were significantly higher than that of rooibos tea in all plants. Salvia africana-caerulea water extract ORAC results were 14147.10±1.02 μmol TE/g and this is 10 times better than the brewed rooibos tea results of 1402±44.1 μmol TE/g. The alpha-amylase enzyme inhibition assay showed no significant results while the alpha-glucosidase enzyme inhibition assays showed significant results in some of the extracts. The highest inhibitory activity towards alpha-glucosidase was found in the Urtica urens hexane extract and the Thymus vulgaris hexane extract (69.66% and 68.43%, respectively). This observation suggests that alpha-glucosidase enzyme is inhibited mostly by the less polar or medium polarity chemical components of the plant extracts. The crude plant extracts that showed significant activity in the antidiabetic bioassays were further subjected to cytotoxicity assay to ascertain the safety of extracts. The T. vulgaris DCM extract, Salvia officinalis DCM extract and Salvia officinalis hexane extract showed a cell growth inhibition of 54.91%, 62.14% and 63.87% at 100 μg/ml, respectively. The Salvia africana-caerulea DCM extract showed a cell growth inhibition of 59.10% at 50 μg/ml and 62.14% at 100 μg/ml. In the cytotoxicity analysis Salvia africana-caerulea DCM extract is the only extract that showed cell viability below 50% for both concentrations. Phytochemical screening of selected methanolic and aqueous extracts of the diabetes tea and the Salvia africana-caerulea showed the presence of alkaloids, sugars, flavonoids, glycosides, proteins & amino acids, phenolics & tannins and saponins. Furthermore isolation, purification and analysis of two Salvia africana-caerulea crude extracts (DCM and DCM:MeOH) were done in order to try and obtain pure compounds. The compound characterization was done through the use of chromatographic techniques. Thin layer chromatography (TLC), flash chromatography and column chromatography resulted in the generation of 29 fractions. Spectroscopic techniques utilized for chemical structural elucidation for compounds of interest included Liquid chromatography mass spectrometry and Nuclear Magnetic Resonance Spectroscopy. Of all the fractions generated, DM 23 was the purest and its structural elucidation was attempted.
Thesis (MTech (Chemistry))--Cape Peninsula University of Technology, 2017
Keywords: Materia medica, Vegetable; Pharmaceutical technology; Diabetes -- Chemotherapy; Phytochemicals; Herbs -- Therapeutic use; Diabetes -- Alternative treatment; Medicinal plants